Reference Values and Related Factors for Peak Expiratory Flow in Middle-Aged and Elderly Chinese - Ji, Chao; Xia, Yang; Dai, Huixu; Zhao, Zhiying; Liu, Tiancong; Tong, Shuhui; Zhang, Xiaohang; Zhao, Yuhong (Frontiers in Public Health, 2021)
Background: Peak expiratory flow (PEF), as an essential index used for screening and monitoring asthma, chronic obstructive pulmonary disease, and respiratory mortality especially in the elderly, is recommended for low-resource settings in low- and middle-income countries. However, few studies have focused on the reference of PEF in China, especially in middle-aged and elderly people. Thus, this study aimed to determine age- and sex-specific reference values of PEF in the middle-aged and elderly Chinese population. Methods: There were 8,914 participants who were included for risk factor analysis and 5,498 participants included for reference value analysis. The PEF was measured using a peak flow meter in liters per minute. The distributions of standardized PEF terciles stratified by sex and age were reported. Multiple linear regression analysis was used to determine the associations between risk factors and PEF. Results: The PEF was higher in men than women across all age subgroups. The value of PEF decreased with age in both men and women. Height, weight, handgrip strength, and residence in rural were positively associated with PEF. Age and smoking status were negatively associated with PEF significantly in both men and women (P < 0.05). The mean PEF values were 367.10 and 253.00 L/min for men and women, respectively. Meanwhile, the prevalence of low PEF was 3.94 and 3.32% for men and women, respectively. Conclusions: Age- and sex-specific centiles of standardized PEF for the middle-aged and elderly Chinese population were estimated. The reference values for low PEF could provide reference standards for epidemiological studies and clinical practices in the future. Interventions to improve lung functions or to prevent respiratory disease should be paid more attention to factors associated with PEF.